2008
DOI: 10.1074/jbc.m800308200
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleolus Exhibits an Osmotically Regulated Gatekeeping Activity That Controls the Spatial Dynamics and Functions of Nucleolin

Abstract: We demonstrate that physiologically relevant perturbations in the osmotic environment rheostatically regulate a gatekeeping function for the nucleolus that controls the spatial dynamics and functions of nucleolin. HeLa cells and U2-OS osteosarcoma cells were osmotically challenged with 100 -200 mM sorbitol, and the intranuclear distribution of nucleolin was monitored by confocal microscopy. Nucleolin that normally resides in the innermost fibrillar core of the nucleolus, where it assists rDNA transcription and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…We therefore manipulated cellular levels of diphosphoinositol polyphosphates in an osteosarcoma cell line using a combination of hyperosmotic stress and some pharmacological tricks (Yang et al, 2008). We found that a hyperosmotic challenge indeed caused nucleolin to accumulate in the nucleoplasm-suggesting its degree of phosphorylation was increased-but this response occurred independently of changes in levels of diphosphoinositol polyphosphates (Yang et al, 2008). Nevertheless, our experiments with nucleolin can only be considered an indirect test of the hypothesis put forward by Saiardi et al (2004) and Bhandari et al (2007).…”
Section: Protein Phosphorylation By Diphosphoinositol Polyphosphates?mentioning
confidence: 85%
See 3 more Smart Citations
“…We therefore manipulated cellular levels of diphosphoinositol polyphosphates in an osteosarcoma cell line using a combination of hyperosmotic stress and some pharmacological tricks (Yang et al, 2008). We found that a hyperosmotic challenge indeed caused nucleolin to accumulate in the nucleoplasm-suggesting its degree of phosphorylation was increased-but this response occurred independently of changes in levels of diphosphoinositol polyphosphates (Yang et al, 2008). Nevertheless, our experiments with nucleolin can only be considered an indirect test of the hypothesis put forward by Saiardi et al (2004) and Bhandari et al (2007).…”
Section: Protein Phosphorylation By Diphosphoinositol Polyphosphates?mentioning
confidence: 85%
“…Thus, the extent to which nucleolin accumulates in the nucleoplasm can be anticipated to provide a measure of its degree of phosphorylation. We therefore manipulated cellular levels of diphosphoinositol polyphosphates in an osteosarcoma cell line using a combination of hyperosmotic stress and some pharmacological tricks (Yang et al, 2008). We found that a hyperosmotic challenge indeed caused nucleolin to accumulate in the nucleoplasm-suggesting its degree of phosphorylation was increased-but this response occurred independently of changes in levels of diphosphoinositol polyphosphates (Yang et al, 2008).…”
Section: Protein Phosphorylation By Diphosphoinositol Polyphosphates?mentioning
confidence: 99%
See 2 more Smart Citations
“…For Kcs1 mutants, the analysis revealed a decrease in the phosphorylation of some nucleolar proteins, including nucleolin (39). However, studies in mammalian cells ruled out the possibility that nucleolin serves as a molecular target for inositol pyrophosphate response to osmotic stress in vivo (40).…”
Section: Discussionmentioning
confidence: 99%